2013
DOI: 10.1007/s11434-012-5627-8
|View full text |Cite
|
Sign up to set email alerts
|

Urbanization and heterogeneous surface warming in eastern China

Abstract: With the homogeneity-adjusted surface air temperature (SAT) data at 312 stations in eastern China for 1979-2008 and the Defense Meteorological Satellite Program/Operational Linescan System (DMSP/OLS) nighttime light data, the spatial heterogeneities of the SAT trends on different scales are detected with a spatial filtering (i.e. moving spatial anomaly) method, and the impact of urbanization in eastern China on surface warming is analyzed. Results show that the urbanization can induce a remarkable summer warmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
45
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 35 publications
4
45
0
1
Order By: Relevance
“…The maximum T 2 changes are usually found in the city centers of the PRD region, with typical increments of over 1.1 • in January and of over 0.5 • in July. These findings are comparable to the values estimated for other cities (Fan and Sailor, 2005;Ferguson and Woodbury, 2007;Zhu et al, 2010;Menberg et al, 2013;Wu and Yang, 2013;Bohnenstengel et al, 2014;Yu et al, 2014;Xie et al, 2016) and can be confirmed by similar research in South China (Meng et al, 2011;Feng et al, 2012Feng et al, , 2014. Figure 4e and f present the vertical changes in air temperature from the surface to the 800 hPa layer along the line AB (shown in Fig.…”
Section: Changes In Surface Energy and Air Temperaturesupporting
confidence: 89%
See 2 more Smart Citations
“…The maximum T 2 changes are usually found in the city centers of the PRD region, with typical increments of over 1.1 • in January and of over 0.5 • in July. These findings are comparable to the values estimated for other cities (Fan and Sailor, 2005;Ferguson and Woodbury, 2007;Zhu et al, 2010;Menberg et al, 2013;Wu and Yang, 2013;Bohnenstengel et al, 2014;Yu et al, 2014;Xie et al, 2016) and can be confirmed by similar research in South China (Meng et al, 2011;Feng et al, 2012Feng et al, , 2014. Figure 4e and f present the vertical changes in air temperature from the surface to the 800 hPa layer along the line AB (shown in Fig.…”
Section: Changes In Surface Energy and Air Temperaturesupporting
confidence: 89%
“…Anthropogenic heat (AH) can increase turbulent fluxes in sensible and latent heat (Oke, 1988), implying that it can modulate local and regional meteorological processes (Ichinose et al, 1999;Block et al, 2004;Fan and Sailor, 2005;Ferguson and Woodbury, 2007;Zhu et al, 2010;Feng et al, 2012Feng et al, , 2014Menberg et al, 2013;Ryu et al, 2013;Wu and Yang, 2013;Bohnenstengel et al, 2014;Chen et al, 2014a;Meng et al, 2011;Yu et al, 2014;Xie et al, 2016) and thereby exert an important influence on the formation and the distribution of ozone (Ryu et al, 2013;Yu et al, 2014;Xie et al, 2016) as well as aerosols (Yu et al, 2014;Xie et al, 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A spatial filtering method described by Wu and Yang (2013) is applied to isolate the heterogeneous climatic forcing of urbanization. More specifically, for each grid a spatial anomaly is defined as the departure from the average value over a region centered at each grid.…”
Section: Model Evaluationmentioning
confidence: 99%
“…It covers an area of 9.96 × 10 4 km 2 , with a total urban area of 4.19 × 10 3 km 2 . Observations have shown that the urban land-use expansion in this region has induced a remarkable warming due to the significant UHI effect (Du et al, 2006;Wu and Yang, 2013;Wang et al, 2015). The annual mean warming reached up to 0.16 • C/10 yr based on station measurements in large cities (Ren et al, 2008), which accounted for 47.1 % of the overall warming during the period of 1961-2000.…”
mentioning
confidence: 99%